EDUCATING PROFESSIONALS FROM ACROSS THE GLOBE TO IMPROVE THE QUALITY OF PALLIATIVE CARE PROVISION; A FULLY ONLINE ACADEMIC PALLIATIVE CARE PROGRAMME. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Stevens, Elaine; Milligan, Stuart
Abstract : The receipt of palliative care at the end of life is an international human right (Brennan 2007). However 32% of countries continue to have no palliative care services (World Palliative Care Alliance 2011) while in countries that have well-developed services these are not equitable (Scottish Government 2008). One key to improving palliative care provision globally is to offer accessible, evidence based palliative care education that meets the needs of professionals from a variety of clinical and geographical locations (Stevens 2008). This poster will present information on a novel multi-professional palliative care programme which is delivered fully online and leads to a recognised academic qualification in palliative care. The poster will identify the programme learning outcomes and detail its content and delivery methodology. The poster will also detail who the programme is aimed at and where, geographically and clinically, past students have come from. The teaching and learning strategies employed that allow students to meet the learning outcomes will be outlined. The main benefits of the programme on individual clinical practice, taken from student evaluations, will also be presented.